Issues of Work in Malaysia: Workforce Development - Shukran Abd. Rahman (IIUM, 2009)
Comprehensive workforce development is imperative in a country like Malaysia, which is currently emphasising the need for a holistically competent workforce. Workforce in the country is expected to live as a united confident Malaysian society, infused with strong moral and ethical values. They are expected to be democratic, liberal, tolerant, caring, and be part of an economically just and equitable society. More importantly, they are expected to collectively strive to contribute to the development of Malaysia and help her to attain the status of a developed country. In supporting this aspiration, Malaysians are expected to continuously equip themselves with competencies so that they could become the main players of the country’s growth. Workforce development in Malaysia is thus an essential item on the agenda that deserves orchestrated efforts.